ASSA13-02-16 Atorvastatin Therapy in Patients with Atrial Fibrillation Ablation to Maintain Sinus Rhythm. (29th April 2013) - Jiang, Fenglin; Zhang, Zhihui; Wang, Xiaoyan; Zeng, Lixiong; Tu, Shan
Abstract : Background: There is little information available on the benefits of selection of statins as upstream therapy for the prevention of paroxysmal atrial fibrillation (AF). Objective: The aim of this study was to investigate recurrence of atrial fibrillation (AF) in patients who will take AF ablation after 7 days, randomised to treatment with atorvastatin 40mg/day or placebo 30.90 and 180 days. Methods: We compared the efficacy and safety of atorvastatin (A-group, n = 51) and placebo (P-group, n = 50) as upstream therapy in patients with paroxysmal AF. A total of 101 patients (56 men, mean age, 65 ± 7 years) were retrospectively assigned to receive atorvastatin 7days before AF ablation (n = 51; 40 mg/day) or placebo (n = 50). Results: Survival rates free from AF recurrence at 1, 3, and 6 months were 93%, 90% and 81% in A-group, and 88%, 73%, and 59%, respectively, in P-group (P = 0.005, A-group versus P-group). Using a logistic regression model, atorvastatin was found to be associated with a significantly reduced risk of AF recurrence in comparison to placebo (unadjusted odds ratio [OR] = 0.25, 95% confidence interval 0.12–0.45, P = 0.005). This association remained significant after adjustment for potentially confounding variables (OR = 0.24, 95% CI 0.10–0.56, P = 0.017) Adverse effects requiring discontinuation of statins were observed in 1 case (2%, myalgia) in A-group, and 1 case (2%, elevation in CPK level ≥ 500 IU/L) in P-group, respectively (P = NS, A-group versus P-group). Conclusions: This randomised study supported that using atorvastatin 7 days before AF ablation was considered to be exactly effective in preventing recurrence of paroxysmal AF.